Analisis Risiko dan Kelayakan Usaha Produk Wirausaha Kembang Goyang dari Daun Kelor - Jaka Darma Jaya (Jurnal Teknologi Agro-Industri, 2023)
Kembang goyang moringa leaves is a traditional cake that was developed as an innovation in entrepreneurship. The development of the Moringa leaf goyang flower business aims to develop the cultural heritage of traditional South Kalimantan cakes, while optimizing the use of local Moringa leaf resources. Therefore, in this research, a study was carried out on the production of the Moringa leaf rocking flower using 3 (three) different formulations, risk and business feasibility analysis, and marketing strategy analysis of Moringa leaf rocking flower. Based on the results of the hedonic test on the kembang goyang moringa leaf product, it is known that the kembang goyang K10 product containing 10 g of moringa leaf flour is the best kembang goyang product in terms of taste, appearance, aroma and texture of the product. Next, a risk analysis was carried out on the Moringa leaf goyang flower business to map and anticipate risks that might occur. It is known that business capital and the availability of Moringa raw materials occupy extreme and high risk levels. The business feasibility analysis shows that the Moringa leaf rocking flower business is feasible to run with an R/C ratio of 1.87% and a PBP of 1.15. In further development, it is necessary to optimize marketing using a segmenting, targeting and positioning approach so that the Moringa leaf goyang flower product is well received by consumers.